Biodiversity conservation in Southeast Asian timber concessions: a critical evaluation of policy mechanisms and guidelines - Dennis, R.A.; Meijaard, E.; Nasi, Robert; Gustafsson, L. (2008)
Tropical deforestation is leading to a loss of economically productive timber concessions, as well as areas with important environmental or socio-cultural values. To counteract this threat in Southeast Asia, sustainable forest management (SFM) practices are becoming increasingly important. We assess the tools and guidelines that have been developed to promote SFM and the progress that has been made in Southeast Asia toward better logging practices. We specifically focus on practices relevant to biodiversity issues. Various regional or national mechanisms now inform governments and the timber industry about methods to reduce the impact of production forestry on wildlife and the forest environment. However, so many guidelines have been produced that it has become difficult to judge which ones are most relevant. In addition, most guidelines are phrased in general terms and lack specific recommendations targeted to local conditions. These might be reasons for the generally slow adoption of SFM practices in the region, with only a few countries having incorporated the guidelines into national legislation. Malaysia, Indonesia, and Laos are among the frontrunners in this process. Overall there is progress, especially in the application of certification programs, the planning and management of high conservation value forests, the regulation and control of hunting, and silvicultural management. To reduce further forest loss, there is a need to accelerate the implementation of good forest management practices. We recommend specific roles for governments, the forestry industry, and nongovernmental organizations in further promoting the implementation of SFM practices for biodiversity conservation.